1991
DOI: 10.1002/qua.560400725
|View full text |Cite
|
Sign up to set email alerts
|

On the inhibition of alcohol dehydrogenase: Shape group analysis of molecular electrostatic potential on van der Waals surfaces for some pyrazole derivatives

Abstract: The assessment of molecular similarity between molecules is a fundamental task in computer-aided drug design. In this work, we have applied a combined analysis of steric and electrostatic properties of a series of inhibitors of liver alcohol dehydrogenase ( LADH) to rationalize their action. The methodology is based on a topological characterization of the distribution of molecular electrostatic potential (MEP) on the fused-sphere van der Waals surface of a molecule. The topological description can be rendered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…It was found that the inhibitory power increases by a factor of 2 for each added methylene group CH 2 of the hydrocarbon substitutes in position 4. 32,36 In Table 1, the lipophilic indices, l s (8) , of hydrocarbon substitutes increase regularly with the number of carbon atoms by an increment of 0.033 per CH 2 , consistent with the experimental observation. In the next section, we focus on the QSAR relationship between molecular bioactivities and lipophilicity indices of pyrazole derivatives.…”
Section: Calculations Of Hmlp Indicessupporting
confidence: 86%
See 3 more Smart Citations
“…It was found that the inhibitory power increases by a factor of 2 for each added methylene group CH 2 of the hydrocarbon substitutes in position 4. 32,36 In Table 1, the lipophilic indices, l s (8) , of hydrocarbon substitutes increase regularly with the number of carbon atoms by an increment of 0.033 per CH 2 , consistent with the experimental observation. In the next section, we focus on the QSAR relationship between molecular bioactivities and lipophilicity indices of pyrazole derivatives.…”
Section: Calculations Of Hmlp Indicessupporting
confidence: 86%
“…The interaction with the metallic cation seems to be essential for the release of the NOH proton to create the bond between pyrazole and NAD. 36,43 HMLP calculations of this research show that nonprotonated nitrogen N(2) is the most hydrophilic atom; therefore, it is easily bound with the zinc cation through electrostatic interaction. It was found that the inhibitory power increases by a factor of 2 for each added methylene group CH 2 of the hydrocarbon substitutes in position 4.…”
Section: Calculations Of Hmlp Indicesmentioning
confidence: 99%
See 2 more Smart Citations
“…Here we shall provide only a brief summary of these results and some of the literature references involving applications of various relevant topological shape analysis methods [17,18,20,49,[51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66]. Shape analysis studies of some macromolecules, including proteins, were the very first to derive high accuracy, quantum chemistry quality electron densities for proteins and for drug molecules such a taxol [17,18,20,55], and for the construction of efficient lipophilicity potentials [49,62].…”
Section: Applicationsmentioning
confidence: 99%